A Py-GC / MS analysis method for micro-nano plastics in atmospheric particulate matter
By introducing a chromatographic peak reconstruction algorithm into the Py-GC/MS analysis method, the problems of internal interference and organic interference in micro-nano plastics in atmospheric particulate matter are solved, and accurate quantitative analysis of micro-nano plastics is achieved, with good reproducibility and accuracy.
Patent Information
- Application Number
- CN202311857780.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-12-29
AI Technical Summary
In the prior art, when analyzing micro-nano plastics in atmospheric particulate matter, there are problems of internal interference between micro-nano plastics and organic matter interference in the sample, resulting in limited accuracy and efficiency of quantitative analysis.
Using a Py-GC/MS analysis method, combined with a chromatographic peak reconstruction algorithm, can solve the problems of internal interference between micro-nano plastics and organic matter interference in samples, and achieve accurate and quantitative analysis of micro-nano plastics in atmospheric particulate matter.
This method can directly measure PET without derivatization and separately measure different micro-nano plastics of the same genus, such as PS and ABS, which have good reproducibility and accuracy, and can effectively remove interfering non-volatile and volatile organic matter and improve recovery.
Smart Images

Figure CN118010860B_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the field of organic detection technology, and in particular to a Py-GC / MS analysis method for micro-nano plastics in atmospheric particulate matter. Background technology:
[0002] Microplastics (1-5μm) and nanoplastics (<1μm) produced by mechanical wear, biodegradation and photochemical aging of plastic products are a new type of pollutants and are widely detected in the environment. Studies have shown that some micro-nano plastics have toxic effects and bioaccumulation, and their environmental exposure will bring certain health risks to the human body. The atmosphere is an important source and sink of micro-nano plastics. On the one hand, atmospheric transmission can bring micro-nano plastics to remote areas, causing environmental pollution; on the other hand, the atmosphere is also one of the most extensive human exposure pathways for micro-nano plastics. Therefore, characterizing the types and concentration levels of micro-nano plastics in the atmosphere plays an extremely important role in understanding their pollution characteristics in the atmospheric environment and assessing the environmental health risks they bring.
[0003] Compared with optical characterization, Py-GC / MS detects the characteristic ions of micro-nano plastic pyrolysis products for qualitative and quantitative analysis. Therefore, this technology is not limited by the complex physical characteristics of micro-nano plastics such as size, shape, density, polymer type and surface characteristics, and can provide more objective characterization results. It has been widely used in the analysis of micro-nano plastics in recent years. However, during the pyrolysis process, different types of micro-nano plastics may produce the same products. For example, PET, PS and PVC can all be pyrolyzed to produce benzene, and PS and PVC can be pyrolyzed to produce indene and naphthalene. Therefore, when these non-specific pyrolysis products are used as quantitative compounds in micro-nano plastic mixtures, the content of some micro-nano plastics will be overestimated. In order to solve this problem, some studies have selected specific pyrolysis products of micro-nano plastics as quantitative ions, but the yield of these specific pyrolysis products is often low, and a large amount of enrichment of environmental samples is required before they can be detected, which increases the time and cost of the experiment. In addition to the internal interference between micro-nano plastics, the organic matter present in environmental samples will also interfere with the quantification of micro-nano plastics (such as natural fats and aromatic compounds in environmental samples, which lead to overestimation of PE and PVC, respectively). Therefore, when using PyGC-MS to measure micro-nano plastics, the sample needs to be pre-treated to remove organic matter. However, the existing pre-treatment methods are mainly aimed at matrices such as soil and sediment, and there is little research on the pre-treatment methods of atmospheric particulate matter.
[0004] In addition to volatile organic compounds such as benzene, indene, and naphthalene, atmospheric particulate matter also contains non-volatile organic compounds such as lignin, cellulose, and hemicellulose. These organic compounds will generate a variety of aromatic compounds during the pyrolysis process, which will interfere with quantification. At the same time, micro-nano plastics in atmospheric particulate matter usually exist in the form of complex mixtures, which brings about the problem of mutual interference between the pyrolysis products of micro-nano plastics. Summary of the invention:
[0005] The present invention solves the problems existing in the prior art and provides a Py-GC / MS analysis method (pyrolysis-gas chromatography / mass spectrometry analysis method) of micro-nano plastics in atmospheric particulate matter. The method proposed in the present invention can solve the problems of internal interference between micro-nano plastics and interference from organic matter in samples, and simultaneously perform qualitative and quantitative analysis of micro-nano plastics in atmospheric particulate matter, thereby realizing accurate determination of different types of micro-nano plastics.
[0006] The object of the present invention is to provide a Py-GC / MS analysis method for micro-nano plastics in atmospheric particulate matter, wherein the micro-nano plastics include PE, PP, PS, ABS, PC, PMMA, PVC and PET, and the method comprises the following steps:
[0007] S1. Preparation of standard samples of micro-nano plastics: Take standard samples of PE, PP, PS, ABS, PC, PMMA, PVC, PET and d-PS, and prepare a mixed solution of dichloromethane (DCM) and tetrahydrofuran (THF) with a volume ratio of 1:1, hexafluoroisopropanol (HFIP), ethyl acetate (EtOAc) and pure silica respectively; add a mixed solution of dichloromethane and tetrahydrofuran to the PS, PVC, PMMA, ABS or PC standard products to prepare the corresponding liquid single standards; add a hexafluoroisopropanol solution to the PET standard product to prepare a PET liquid single standard; add an ethyl acetate solution to the d-PS standard product to prepare a d-PS liquid single standard; add silica to the PE or PP standard product to prepare the corresponding solid single standard. The d-PS liquid single standard is used as a quantitative internal standard to correct the error in the thermal cracking process;
[0008] S2. Selection of quantitative compounds for micro-nano plastics: Select 8 quantitative compounds for micro-nano plastics and d-PS internal standards;
[0009] S3, placing the standard sample to be tested into a pyrolysis container, adding d-PS internal standard in a mass ratio of 50:1 between the standard sample to be tested and the d-PS internal standard, after the internal standard solvent evaporates, placing the pyrolysis container into the cracker, and when the cracker temperature reaches 290°C-310°C, the pyrolysis container enters the heating zone of the cracker, bakes the sample for 1.5-2.5 minutes and then pulls it out, and after heating the cracker to 580°C-600°C, pushes down the injection rod again and starts GC / MS for data acquisition at the same time, and obtains the Py-GC / MS total ion flow diagram of the sample;
[0010] S4, measuring the solid / liquid single label configured in step S1 according to the measurement conditions of step S3 by using a chromatographic peak reconstruction algorithm, and extracting the quantitative compound selected in step S2 from the total ion current graph of each single label;
[0011] The implementation steps of the algorithm are as follows:
[0012] (1) A series of mass gradient micro-nano plastic mixed standard samples were prepared by adding six liquid single standards of PS, ABS, PC, PMMA, PVC, and PET in different volumes and two solid single standards of PE and PP in different masses. The micro-nano plastic mixed standard samples were analyzed by Py-GC / MS. The quantitative compound ion chromatograms of the mutually interfering micro-nano plastics and internal standards were extracted from the total ion flow diagram, and the response factor of each quantitative compound was calculated (response factor = quantitative compound peak area / internal standard peak area). The quantitative compound response factors of the mutually interfering micro-nano plastics can form a matrix.
[0013] (2) Py-GC / MS was used to analyze a series of mass gradient single standards of five mutually interfering micro-nano plastics, namely PE, PS, ABS, PVC and PET. The quantitative compound ion chromatograms of the five mutually interfering micro-nano plastics and the internal standard were extracted from all total ion currents. Assuming that the yields of all pyrolysis products during the pyrolysis of micro-nano plastics were constant, a linear equation for the response factor ratio of the quantitative compound of the micro-nano plastic and other quantitative compounds of the generated micro-nano plastics was established based on the series of mass gradient single standards of each micro-nano plastic. The linear equation group of the response factor ratio of mutually interfering micro-nano plastics constituted a non-specific quantitative compound source contribution matrix.
[0014] (3) Assuming that the nonspecific pyrolysis products in the micro-nano plastic mixture are mainly derived from the linear combination of the pyrolysis contributions of the mutually interfering micro-nano plastics, the mutually interfering micro-nano plastic quantitative compound response factor matrix obtained from the micro-nano plastic mixed standard and the nonspecific quantitative compound source contribution matrix obtained from the single standard are solved. The result is the chromatographic peak reconstruction matrix, that is, the actual quantitative compound response factor matrix of the mutually interfering micro-nano plastics; the matrix has a unique solution, and all unknowns are positive (that is, the actual quantitative ion response factor of the polymer has no negative contribution);
[0015] (4) Repeatedly solve the chromatographic peak reconstruction matrix of each mass gradient micro-nano plastic mixed standard sample, and establish a quantitative standard curve for each micro-nano plastic with the actual quantitative compound response factor of the micro-nano plastic as the horizontal coordinate and the mass as the vertical coordinate;
[0016] S5. Add digestion solution to the atmospheric particulate matter sample for digestion. After digestion is completed, filter the sample and freeze-dry it for analysis;
[0017] S6. Detect the atmospheric particulate matter sample obtained in step S5 according to the detection conditions of step S3, and perform qualitative and / or quantitative analysis on the Py-GC / MS total ion current diagram of the obtained atmospheric particulate matter sample.
[0018] In step S1, the six liquid single standards of PS, PVC, PMMA, ABS, PC and PET are placed in an ultrasonic instrument for ultrasonic treatment to ensure that the standard is fully dissolved in the solution. A certain amount of silica is placed in the vector-selected PE and PP standards to prepare corresponding solid single standards, and the two solid single standards are fully ground using a cryogenic grinder to ensure full homogenization.
[0019] The analytical method proposed in the present invention proposes a chromatographic peak reconstruction algorithm that can reconstruct the non-specific product chromatographic peak in the micro-nano plastic mixture into a linear combination of micro-nano plastic types that can generate the product, and the algorithm is used in combination with a standard sample of the micro-nano plastic mixture to establish a quantitative standard curve. For a micro-nano plastic mixture of known mass, the average quantitative accuracy of the algorithm reaches 89%. The method is used to process a quartz fiber filter membrane added with a known mass of micro-nano plastic mixture, and the sample data is processed and quantified using the chromatographic peak reconstruction algorithm. The results show that the recovery rate of 8 types of micro-nano plastics in the spiked sample is between 63% and 97%. The chromatographic peak reconstruction algorithm proposed in the present invention can avoid the quantitative error caused by selecting non-specific products as quantitative ions, can directly determine PET without derivatization, and can separately determine different micro-nano plastics of the same genus, such as PS and ABS, with good reproducibility and accuracy; the digestion pre-treatment method proposed in the present invention can remove interfering non-volatile organic matter (such as lignin) and volatile organic matter (such as benzene) in atmospheric particulate matter, and has a good recovery rate.
[0020] Preferably, in step S1, the liquid single-label concentrations of PS, PVC, PMMA, ABS, PC and PET are all 1.0-1.5 μg / μL, and the solid single-label concentrations of PP and PE are all 2-4 μg / mg. More preferably, the liquid single-label concentrations of PS, PVC, PMMA, ABS, PC and PET are all 1.2 μg / μL, the solid single-label concentrations of PP are all 2 μg / mg, and the solid single-label concentrations of PE are all 4 μg / mg.
[0021] Preferably, in step S2, the quantitative compound of PE is 1-eicosene (m / z=83), the quantitative compound of PP is 2,4-dimethyl-1-1 heptene (m / z=126), the quantitative compound of PS is 1,3,5-triphenyl-5-hexene (m / z=91), the quantitative compound of ABS is 4-phenyl-4-pentenenitrile (m / z=157), the quantitative compound of PC is p-isopropenylphenol (m / z=134), the quantitative compound of PMMA is methyl methacrylate (m / z=100), the quantitative compound of PVC is indene (m / z=116), the quantitative compound of PET is benzene (m / z=78), and the quantitative compound of internal standard d-PS is styrene-D7 (m / z=111).
[0022] Preferably, the GC / MS detection conditions in step S3 are: using a non-polar DB-5MS 30m×0.25mm×0.25μmAgilent Technologies, Santa Clara, CA Clara, USA was used as the chromatographic column, the injection port temperature was 280°C, the helium flow rate was 1.1mL / min, the split ratio was 5:1, and the carrier gas was high-purity helium; the heating program was as follows: initial temperature 40°C, maintained for 2min, increased to 250°C at a rate of 5°C / min, maintained for 1min, then increased to 300°C at a rate of 1.5°C / min, maintained for 5min; the ion source used the electron impact ionization source (EI) mode, the ion source temperature was 250°C, the transmission line temperature was 295°C, the acquisition mode was the scan mode, the scanning range was 50-550m / z, and the solvent delay time was 1.2min; the multi-shot pyrolysis instrument was set as follows: thermal desorption at 300°C for 2min, then increased to 590°C, thermal pyrolysis for 1min, and the interface temperature was 300°C.
[0023] The pyrolysis conditions in step S3 are as follows: when the temperature of the cracker reaches 300°C, the pyrolysis container enters the heating zone of the cracker, bakes the sample for 2 minutes and then pulls it out. After the cracker is heated to 590°C, the injection rod is pushed down again and GC / MS is started for data acquisition at the same time to obtain the Py-GC / MS total ion flow diagram of the sample at 590°C.
[0024] Preferably, the quantitative standard curve of each micro-nano plastic in step S4 is shown in the following table:
[0025]
[0026]
[0027] In step S4, the solid / liquid single standard configured in step S1 is measured according to the measurement conditions of step S3 by the chromatographic peak reconstruction algorithm, and the quantitative compounds selected in step S2 are extracted from the total ion current diagram of each single standard. The results show that the selected quantitative compounds of PE, PP, PMMA, PC and ABS are their own specific pyrolysis products, and there is no mutual interference. The selected quantitative compounds of PS, PET and PVC are non-specific pyrolysis products. PS, ABS and PVC can produce a large amount of indene by pyrolysis, so PS and ABS are considered to be polymers that interfere with PVC; ABS pyrolysis can also produce a large amount of 1,3,5-triphenyl-5-hexene, so ABS is considered to be a polymer that interferes with PS; PP, PS, ABS, PVC and PET pyrolysis can produce a large amount of benzene, so PP, PS, ABS and PVC are considered to be polymers that interfere with PS. The present invention proposes an algorithm for chromatographic peak reconstruction, the core assumption of which is that the non-specific pyrolysis product chromatographic peak in the micro-nano plastic mixture is contributed by the micro-nano plastic that can be pyrolyzed to generate the product, and these contributions are linearly related.
[0028] Preferably, the digestion solution in step S5 is nitric acid, trifluoroacetic acid or hydrogen peroxide, and the volume concentration of the digestion solution is 26%-65%.
[0029] The specific steps of step S5 are as follows: In order to prevent the volatilization of the solution during the digestion process and reduce the influence of the external environment, the present invention chooses to use an ampoule-digestion tank device for digestion. After the sample is placed in the ampoule, the digestion solution is added, and the mouth of the ampoule is heated to seal it. The sealed ampoule is placed in the inner tank, and 150μL of water is added to balance the pressure difference between the inside and the outside to prevent the ampoule from exploding. The inner tank is placed in the stainless steel outer tank, and after tightening the outer tank, it is placed in an oven for heating. After the digestion is completed, take out the digestion tank, and take out the ampoule after cooling to room temperature. Place a 0.22μm glass fiber filter membrane with a diameter of 2.5cm in the filtration device and connect it to a vacuum pump. Use a glass dropper to transfer the solution in the ampoule to the filtration device, rinse the ampoule with ultrapure water and transfer it to the filtration device, turn on the vacuum pump to pump the solution in the upper part of the device into the lower conical flask, rinse the upper device with ultrapure water, remove the glass fiber filter membrane after drying, and store it in clean aluminum foil. Use a cold dryer to dry the filter membrane, and after the cold drying is completed, use Py-GC / MS for analysis according to step S3.
[0030] Preferably, the ratio of the atmospheric particulate matter sample to the digestion solution is: 1.04-2.6 mL of the digestion solvent is added to 1 mg of the atmospheric particulate matter sample.
[0031] Preferably, the digestion time is 2-6 hours and the digestion temperature is 60°C-100°C.
[0032] The specific steps of step S6 are: use an active atmospheric sampler to collect atmospheric particulate matter samples, and the atmospheric particulate matter is collected on a quartz fiber filter membrane that has been pre-baked at 450°C for 6 hours. Use a cylindrical stainless steel cutter to evenly cut a plurality of small circular membranes of equal area from the quartz fiber filter membrane sample, and tear off the surface samples of the small circular membranes for digestion. Digestion is performed according to step S5, and Py-GC / MS is performed according to step S3. Qualitative and / or quantitative analysis is performed on the Py-GC / MS total ion current diagram of the atmospheric particulate matter sample obtained in step S3.
[0033] Preferably, the qualitative and / or quantitative analysis of the Py-GC / MS total ion current diagram of the atmospheric particulate matter sample obtained in step S6 is specifically as follows:
[0034] Qualitative analysis: extract the quantitative compound ion chromatogram of each micro-nano plastic selected in step S2 from the Py-GC / MS total ion current graph. If the corresponding quantitative compound ion can be extracted, it means that the sample contains the micro-nano plastic;
[0035] Quantitative analysis: For the five micro-nanoplastics, PE, PP, PMMA, PC and ABS, the quantitative compound ion chromatograms of these five micro-nanoplastics and the internal standard are extracted from the total ion current map, the response factor of each quantitative compound is calculated, and the response factor is substituted into the corresponding micro-nanoplastic quantitative standard curve in step S4 to obtain the mass of the micro-nanoplastic in the sample; for the three micro-nanoplastics, PET, PVC and PS, the quantitative compound ion chromatograms of these three micro-nanoplastics and the internal standard are extracted from the total ion current map, the quantitative compound response factors of the three micro-nanoplastics and their corresponding mutually interfering micro-nanoplastics are calculated, and the quantitative compound response factor matrix of the mutually interfering micro-nanoplastics and the corresponding non-specific quantitative compound source contribution matrix in step S4 are solved to obtain the actual quantitative compound response factors of the mutually interfering micro-nanoplastics in the sample, which are substituted into the corresponding micro-nanoplastic quantitative standard curve in step S4 to obtain the mass of the micro-nanoplastic in the sample.
[0036] The present invention also protects the application of the analytical method in determining micro-nano plastics in atmospheric particulate matter, and the micro-nano plastics include PE, PP, PS, ABS, PC, PMMA, PVC and PET.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. The present invention can directly measure the concentration of microplastics and nanoplastics in atmospheric particulate matter, is not limited by the complex physical characteristics of microplastics such as size, shape, density, polymer type and surface properties, and can provide more objective characterization results.
[0039] 2. The chromatographic peak reconstruction algorithm proposed in the present invention can avoid quantitative errors caused by selecting non-specific products as quantitative compounds, and has good reproducibility and accuracy.
[0040] 3. The chromatographic peak reconstruction algorithm of the present invention can be used to directly determine PET without the need for an additional derivatization step.
[0041] 4. The chromatographic peak reconstruction algorithm of the present invention can separately measure different micro-nano plastics of the same type, such as PS and ABS.
[0042] 5. The pretreatment method proposed in the present invention can remove non-volatile organic matter (such as lignin) and volatile organic matter (such as benzene) that interfere with the quantification of micro-nano plastics, and has a good recovery rate. Description of the drawings:
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0044] Figure 1 The retention time of the quantitative compound ion peaks of each micro-nanoplastic in the Py-GC / MS total ion current diagram of the micro-nanoplastic mixed standard is shown.
[0045] Figure 2 This is a diagram showing the principle and process of the chromatographic peak reconstruction algorithm. The diagram shows the application of the chromatographic peak reconstruction algorithm in reconstructing and quantifying PS and PVC.
[0046] Figure 3 The results show the average quantitative accuracy of the chromatographic peak reconstruction algorithm for four interfering micro-nanoplastics in the micro-nanoplastic mixture.
[0047] Figure 4 It is a digestion experiment device; wherein, A: ampoule bottle-digestion tank (inner tank: polytetrafluoroethylene material; outer tank: stainless steel material); B: filtration device.
[0048] Figure 5 Shows the removal effect of different digestion solutions on organic mixtures under the same digestion conditions; A: removal effect of organic mixtures in H2O2 digestion group; B: removal effect of organic mixtures in HF3 digestion group; C: HNO3 digestion group and blank control group.
[0049] Figure 6 It is the quantitative compound ion peak response diagram of each micro-nano plastic in the HNO3 digestion group.
[0050] Figure 7 The results show the average recovery rate of each micro-nano plastic at different digestion temperatures under a digestion time of 6h and a 65% HNO3 concentration.
[0051] Figure 8 Shows the removal effect of different digestion temperatures on organic matter mixtures at 6h digestion time and 65% HNO3 concentration; A: removal effect of 60℃ digestion group; B: blank control.
[0052] Fig. 9 The average recovery rate results of various micro-nano plastics at different digestion times at 60°C digestion temperature and 65% HNO3 concentration.
[0053] Fig.10 Shows the removal effect of organic matter mixture at different digestion times at 60℃ digestion temperature and 65% HNO3 concentration; A: removal effect of 2h digestion group; B: blank control group.
[0054] Fig.11 The average recovery results of various micro-nano plastics at 32.5% HNO3 concentration and 65% HNO3 concentration under 60°C digestion temperature and 2h digestion time.
[0055] Fig.12 It shows the removal effect of different HNO3 concentrations on the organic mixture at a digestion temperature of 60℃ and a digestion time of 2h; A: the removal effect of the organic mixture of the 32.5% HNO3 digestion group; B: the removal effect of the organic mixture of the 26% HNO3 digestion group; C: the blank control group.
[0056] Fig.13 Shown are the average recovery results for eight matrix spiked samples fortified with known masses of a mixture of micro- and nanoplastics.
[0057] Fig.14 This is a diagram of the 9-point sampling effect in actual atmospheric particulate matter samples.
[0058] Fig.15 is the total concentration of micro-nano plastics in 5 parallel samples of atmospheric particulate matter.
[0059] Fig.16 Shows the proportion of different micro-nano plastics in 5 parallel samples of atmospheric particulate matter; A: the proportion of different micro-nano plastics in atmospheric samples when the X-axis is set to 0-100%; B: the proportion of different micro-nano plastics in atmospheric samples when the X-axis is set to 0-20%. Specific implementation method:
[0060] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0061] In order to make the purpose, technical solutions and advantages of the present invention clearer, the embodiments and implementation schemes of the present invention will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one example is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0062] Example 1 Preparation of micro-nano plastic standard samples
[0063] The method for configuring micro-nano plastic standard samples of moderate concentration is the mass method. The weight of the required micro-nano plastic pure substance and solvent / matrix is calculated according to the required volume / mass of the micro-nano plastic standard sample, and weighed with a high-precision balance (Sartorius, ±0.0001g). Among them, PS, PVC, PMMA, ABS and PC pure substances are respectively configured into corresponding liquid single standards using a mixed solution of DCM:THF (v:v=1:1); PET pure substances are configured into PET liquid single standards using HFIP solution; d-PS pure substances are configured into d-PS liquid single standards using EtOAc solution, and the above 6 liquid single standards are placed in an ultrasonic instrument for 30 minutes to ensure that the standard is fully dissolved in the solution. PE and PP standards are respectively configured into corresponding solid single standards using silicon dioxide, and these two solid single standards are fully ground using a frozen grinder (Frontier) to ensure full homogenization. Table 1 below shows the concentrations of the 8 micro-nano plastic standards configured in this implementation case and the required solvent / matrix weights.
[0064] Table 1. Single standard concentrations of 8 types of micro-nano plastics
[0065]
[0066]
[0067] Example 2 Selection of qualitative and quantitative compounds for micro-nano plastics
[0068] Select 8 kinds of micro-nano plastics and d-PS internal standard qualitative compounds and quantitative compounds, mainly selected as the pyrolysis product with high yield. The specific pyrolysis product of PET is benzoic acid, but its analysis effect in gas chromatography is poor, so it is often necessary to add tetramethylammonium hydroxide (TMAH) before injection for pyrolysis in situ derivatization, and use the derivatized product dimethyl terephthalate as the quantitative compound of PET. Considering that the efficiency of PET derivatization in each sample is difficult to evaluate, and the error caused by the different TMAH derivatization efficiency may be introduced, the present invention does not perform derivatization operation, but selects the initial pyrolysis products of PET, biphenyl and benzene, as the qualitative compound and quantitative compound of PET respectively. Table 2 below shows the qualitative compounds and quantitative compounds of 8 kinds of micro-nano plastics, wherein the pyrolysis products shown in bold are the quantitative compounds of the corresponding plastics, the ones not shown in bold are the qualitative compounds of the corresponding plastics, and the characteristic ions shown in bold are the quantitative ions of the corresponding quantitative compounds. When judging whether a sample contains this kind of micro-nano plastic, it is necessary to extract the qualitative compounds and quantitative compounds of the micro-nano plastics in the total ion flow diagram at the same time.
[0069] Table 2. Qualitative and quantitative compounds of 8 micro-nano plastics
[0070]
[0071]
[0072] Example 3 Application and evaluation of chromatographic reconstruction algorithm
[0073] (1) Instrument conditions: The Double-Shot-Py-GC / MS analysis system consists of an Agilent 7890-5975 gas chromatograph-mass spectrometer and an EGA / PY-3030D multi-shot pyrolysis instrument. The ion source uses the electron impact ionization source (EI) mode. The non-polar DB-5MS (30m×0.25mm×0.25μm) (Agilent Technologies, Santa Clara, USA) is used as the chromatographic column, the inlet temperature is 280°C, the helium flow rate is 1.1mL / min, the split ratio is 5:1, and the carrier gas is high-purity helium. The heating program is an initial temperature of 40°C, maintained for 2min, increased to 250°C at a rate of 5°C / min, maintained for 1min, and then increased to 300°C at a rate of 1.5°C / min and maintained for 5min. The ion source temperature was 250°C, the transfer line temperature was 295°C, the acquisition mode was scan mode, the scan range was 50-550 m / z, and the solvent delay time was 1.2 min. The multi-shot pyrolysis instrument was set to: thermal desorption at 300°C for 2 min, then increased to 590°C, thermal pyrolysis for 1 min, and the interface temperature was 300°C.
[0074] (2) Py-GC / MS analysis: The sample to be tested is placed in a pyrolysis cup, and a certain amount of d-PS internal standard is added using an injection needle. The mass ratio of the sample to be tested to the d-PS internal standard is 50:1. After the internal standard solvent evaporates, the pyrolysis cup is fixed on the injection rod and loaded into the pyrolysis chamber. When the temperature of the pyrolysis chamber reaches 300°C, the injection rod is pushed down, and the pyrolysis cup enters the heating zone of the pyrolysis chamber. After baking the sample for 2 minutes, the injection rod is pulled out. After the pyrolysis chamber is heated to 590°C, the injection rod is pushed down again and GC / MS is started for data acquisition at the same time to obtain the Py-GC / MS total ion flow diagram of the sample at 590°C.
[0075] (3) Preparation of standard samples and establishment of standard curve
[0076] Each standard sample of micro-nano plastics was placed in a pyrolysis cup, and a syringe was used to add 5 μL of the d-PS internal standard prepared in Example 1. After the internal standard solvent evaporated, the pyrolysis cup was fixed on the injection rod, loaded into the pyrolyzer, and Py-GC / MS analysis was performed according to step (2).
[0077] The single standard prepared in Example 1 was measured in different volumes / masses by a syringe / high-precision balance (Sartorius, ±0.0001g), and different mass gradient single standards were obtained by dilution. In this embodiment, the mass gradient of each single standard is 5, and the gradient range is shown in Table 3. The single standards of each mass gradient of the 8 micro-nano plastics were mixed with each other to form a mixed standard, which also contained 5 mass gradients. A quantitative curve was established with the 5 micro-nano plastic mixed standards, and the micro-nano plastic mixed standards were analyzed by Py-GC / MS according to step (2). The quantitative compounds selected in Example 2 were extracted from the obtained total ion flow chart. The results are shown in FIG. Figure 1 shown.
[0078] For the micro-nano plastics PE, PP, PMMA, PC and ABS whose quantitative compounds are specific pyrolysis products, the quantitative standard curve uses the response factor of the quantitative compound in the five gradients as the horizontal coordinate and the actual weight of the micro-nano plastics corresponding to the five gradients as the vertical coordinate. The final quantitative curve results are shown in Table 3. For PVC, PET and PS whose quantitative compounds are non-specific pyrolysis products, the method for establishing the standard curve is shown below.
[0079] Table 3. Quantitative standard curves of various micro-nano plastics
[0080]
[0081]
[0082] (4) Application of chromatographic reconstruction algorithm
[0083] The characteristic ion chromatogram of the quantitative compound selected in Example 2 is extracted from each single-label total ion current diagram obtained in step (2). The results show that the selected quantitative compounds of PE, PP, PMMA, PC and ABS are all specific pyrolysis products of themselves, and there is no mutual interference. The selected quantitative compounds of PS, PET and PVC are non-specific pyrolysis products, among which PE, PS, ABS, PVC and PET can produce benzene by pyrolysis, so these five micro-nano plastics are mutually interfering micro-nano plastics; PS, ABS and PVC can produce a large amount of indene by pyrolysis, so PS, ABS and PVC are mutually interfering micro-nano plastics; PS and ABS both produce a large amount of 1,3,5-triphenyl-5-hexene by pyrolysis, so PS and AB are mutually interfering micro-nano plastics.
[0084] In order to solve the problem of mutual interference of non-specific pyrolysis products, the present invention intends to use a chromatographic peak reconstruction algorithm to restore the contribution of each mutually interfering micro-nano plastic to the non-specific pyrolysis products in the micro-nano plastic mixture. The chromatographic peak reconstruction algorithm process and examples are as follows Figure 1 As shown in the figure, an example is given of the chromatographic peak reconstruction process of PVC quantitative compounds and PS quantitative compounds.
[0085] ① Analyze the multi-gradient MNPs mixture standard sample (0.2-20 μg) using Py-GC / MS according to the method in step (2). Extract the quantitative compound ion chromatograms of the mutually interfering micro-nano plastics and internal standards from the total ion flow chart, calculate the response factor of each quantitative compound, and calculate the response factor of each micro-nano plastic quantitative compound by formula 1. Figure 2 In the chromatographic reconstruction example of (Box 1), the response factor matrix S (S = [0.6464, 0.3808, 0.02105]) of three mutually interfering micro-nanoplastic quantitative compounds (indene; 1,3,5-triphenyl-5-hexene; 4-phenyl-4-pentenenitrile) can be obtained from the micro-nanoplastic mixed standard.
[0086] ② According to the method of step (2), use Py-GC / MS to analyze a series of mutually interfering microplastic single standards with mass gradients. Extract the quantitative compound ion chromatograms of mutually interfering micro-nanoplastics and internal standards in the total ion current graph. Assume that the yields of all pyrolysis products during the pyrolysis of micro-nanoplastics are constant. Therefore, based on the series of mass gradient single standards of each micro-nanoplastic, a linear equation for the response factor ratio of this type of micro-nanoplastic quantitative compound and other micro-nanoplastic quantitative compounds generated by it can be established. The linear equation group of response factor ratios of mutually interfering micro-nanoplastics constitutes the contribution matrix of non-specific quantitative compound sources. Figure 2In the reconstruction example of (Box 2), the response factor ratio equation of 1,3,5-triphenyl-5-hexene-indene can be obtained from the multi-gradient single standard of PS (see Table 4); the response factor ratio equation of 4-phenyl-4-pentenenitrile-indene and the response factor ratio equation of 4-phenyl-4-pentenenitrile-1,3,5-triphenyl-5-hexene can be obtained from the multi-gradient single standard of ABS (see Table 4). The response factor ratio equation of indene can be obtained from the multi-gradient standard of PVC polymer. Therefore, the linear equation group of the response factor ratios of the three mutually interfering micro-nanoplastics constitutes a 3×3 non-specific quantitative compound source contribution matrix Y (Y=[1,0.2328,1.5242;0,1,6.3122;0,0,1]).
[0087] ③ Assume that the chromatographic peaks of nonspecific pyrolysis products in the micro-nanoplastic mixture mainly come from the linear combination of the pyrolysis contributions of the mutually interfering micro-nanoplastics. Therefore, the quantitative compound response factor matrix of mutually interfering micro-nanoplastics obtained from the micro-nanoplastic mixed standard and the nonspecific quantitative compound source contribution matrix obtained from the single standard are solved to obtain the chromatographic peak reconstruction matrix, which is the actual quantitative compound response factor matrix of mutually interfering micro-nanoplastics. This matrix has a unique solution, and all unknowns are positive (that is, the actual quantitative ion response factor of the polymer has no negative contribution). Figure 2 In the reconstruction example, the mutually interfering micro-nano plastic quantitative compound response factor matrix S and the non-specific quantitative compound source contribution matrix Y ( Figure 2 Box 3), we can get the chromatographic peak reconstruction matrix X( Figure 2 Box 4). Matrix X is the actual quantitative ion response factors of the interfering polymers. Matrix X is solved using the least squares estimation, and the calculation is implemented by R language programming software.
[0088] ④ Repeatedly solve the chromatographic peak reconstruction matrix of each mass gradient micro-nano plastic mixed standard, and establish a quantitative standard curve with the actual quantitative compound response factor of micro-nano plastic as the horizontal coordinate and the mass as the vertical coordinate. The final quantitative curve results are shown in Table 3.
[0089] ⑤Analyze the samples of micro-nano plastic mixtures with known mass, and use the chromatographic peak reconstruction algorithm to obtain the actual quantitative compound response factors of each mutually interfering micro-nano plastic. Calculate its actual mass in the micro-nano plastic mixture through the quantitative standard curve. The accuracy determination uses formula 2 to test the accuracy of the method ( Figure 2 Box 6).
[0090] ⑥ After the accuracy test of the quantitative standard curve is passed, the actual environmental sample is analyzed by Py-GC / MS according to the method of step (2). The chromatographic peak reconstruction algorithm is used to obtain the actual quantitative compound response factor of each mutually interfering micro-nano plastic in the actual sample, and the mass of each mutually interfering micro-nano plastic in the actual environmental sample is calculated by the quantitative standard curve ( Figure 2 Box 7).
[0091]
[0092]
[0093] Table 4. Response factor ratio equations between mutually interfering micro-nano plastics
[0094]
[0095] (5) Method accuracy evaluation
[0096] In order to verify the accuracy of the method, samples of micro-nano plastic mixtures with different known masses (n=8) were used for verification. Double-click Py-GC / MS analysis was performed according to the operation of step (2), and the chromatographic peaks of PS, ABS, PVC and PET were reconstructed according to the operation of step 3. The quantitative standard curves obtained in steps (2) and (3) were used to quantify PS, ABS, PVC and PET, and the accuracy was calculated using formula 2.
[0097] The results are as follows Figure 3 As shown in the figure, the calculated masses of PS, ABS, PVC and PET in the micro-nano plastic mixture are close to the expected masses, and the accuracy rates are between 63.64%-131.67%, 83.31%-116.29%, 83.48%-104.13% and 80.00%-118.74%, respectively. The average accuracy rates of PS, ABS, PVC and PET are 89.26%±21.74%, 89.90%±11.23%, 89.49%±7.63% and 89.17%±12.61%, respectively, and the average relative errors are all less than 25%, indicating that the standard curve established by the chromatographic peak reconstruction algorithm combined with the micro-nano plastic mixed standard has high accuracy and stability for the quantification of mutually interfering micro-nano plastics in the micro-nano plastic mixture, and can be used for the quantification of micro-nano plastics in actual environmental samples.
[0098] Embodiment 4 digestion method
[0099] In order to prevent the volatilization of the solution during the digestion process and reduce the impact of the external environment, this embodiment chooses to use an ampoule-digestion tank device for digestion. After the sample is placed in the ampoule, the digestion solution is added, and the mouth of the ampoule is heated to seal it. The sealed ampoule is placed in the inner tank, and 150 μL of water is added to balance the pressure difference between the inside and the outside to prevent the ampoule from exploding. The inner tank is placed in the stainless steel outer tank, and the outer tank is tightened and placed in an oven to heat ( Figure 4 .A). After digestion is completed, remove the digestion tank and remove the ampoule after cooling to room temperature. Place a 0.22μm glass fiber filter with a diameter of 2.5cm in the filtration device and connect it to a vacuum pump. Use a glass dropper to transfer the solution in the ampoule to the filtration device, rinse the ampoule with ultrapure water and transfer it to the filtration device ( Figure 4 B), turn on the vacuum pump to pump the solution in the upper part of the device into the lower conical flask, rinse the upper device with ultrapure water, remove the glass fiber filter membrane after drying, and store it in clean aluminum foil. Use a cold dryer to dry the filter membrane. After the cold drying is completed, perform Py-GC / MS analysis according to the method of step (2) in Example 3.
[0100] Example 5 Selection of digestion solution
[0101] This example attempts to use the mainstream acid method and oxidant method at home and abroad for digestion. The acid method digestion selects strong oxidizing nitric acid (HNO3) and weak oxidizing trifluoroacetic acid (TFA) as the digestion solution; the oxidant method selects hydrogen peroxide (H2O2) as the digestion solution. The selected digestion solution is finally determined by evaluating the removal effect of the stable organic mixture (lignin, hemicellulose and cellulose). Add 3 portions of excess organic mixture (0.5 mg) to the ampoule, and then measure 2 mL of HNO3, TFA and H2O2 respectively and add them to the ampoule. Take another ampoule without adding organic mixture and digestion solution as a blank control, seal all ampoules, put them into the digestion tank and put them into the oven for heating. The digestion temperature is 100 ° C and the digestion time is 6h. After the digestion is completed, filter and freeze according to Example 4, and perform double-click Py-GC / MS analysis according to the operation of step (2) in Example 3.
[0102] The removal effects of different digestion solutions on organic matter mixtures under the same digestion conditions are as follows: Figure 5As shown. The TIC graph of the H2O2 digestion group has an obvious matrix effect, and extracted ion peaks related to a variety of micro-nano plastic quantitative compounds, such as benzene, styrene, indene and naphthalene. Therefore, it is believed that H2O2 digestion has a poor removal effect on organic mixtures. The TIC graph of the TFA digestion group contains a large number of highly responsive impurity peaks, and also extracted a variety of micro-nano plastic quantitative compound ion peaks. Therefore, it is believed that TFA digestion cannot completely remove organic mixtures. The TIC graph of the HNO3 digestion group has fewer impurity peaks and very low responses, which is similar to the blank control group. Extract all micro-nano plastic quantitative compound ion peaks ( Figure 6 ) and compared with the blank control group, it was found that the response of these quantitative ions was at the same order of magnitude as the blank control group, and the effect on the quantification of micro-nano plastics was very small, so it was believed that it was mainly caused by the pollution introduced during the experiment. Compared with the H2O2 and TFA digestion groups, the present invention believes that HNO3 digestion can completely remove the organic mixture, so it is selected as the digestion solution.
[0103] Example 6 Selection of digestion temperature
[0104] In order to obtain the best recovery rate, this embodiment sets a series of digestion temperature gradients, compares the removal effect of the organic mixture and the recovery rate of micro-nano plastics at each temperature, and thus obtains the optimal digestion temperature.
[0105] ① Prepare a micro-nano plastic mixed standard sample according to the method of Example 1;
[0106] ② When the digestion time and 2mLHNO3 concentration remain unchanged, a 100℃ digestion group (n=4), an 80℃ digestion group (n=4), a 60℃ digestion group (n=4) and a process blank control group are set up. The known micro-nano plastic mixed standard sample of each digestion group is placed in an ampoule bottle, and the digestion method is as shown in Example 4. The lyophilized sample is subjected to Py-GC / MS analysis according to step (2) of Example 3. The obtained total ion current of the sample is quantified according to steps (3) and (4) of Example 3, and the recovery rate is calculated according to formula 3. The final result is as follows: Figure 7 The removal effect of the organic mixture was investigated at each digestion temperature. The operation steps were as shown in Example 5. The removal effect was as shown in Example 5. Figure 8 shown.
[0107]
[0108] The results show that when the digestion time is 6h and the HNO3 concentration is 100%, the organic matter can be completely removed by digestion at 100℃, 80℃ and 60℃. When the digestion temperature is reduced to 80℃, the recovery rates of all micro-nano plastics are significantly improved, among which the recovery rates of PS, ABS, PMMA and PC are the most significantly improved, with the average recovery rates reaching 24.8±7.9, 15.4±2.6, 24.3±3.1 and 63.8±5.9%, respectively. The average recovery rates of PE, PP and PVC are all over 60%, but the average recovery rate of PET is still low (18.0±2.4%). When the digestion temperature is reduced from 80℃ to 60℃, the average recovery rates of PE, PP, PC and PVC do not change much, but the average recovery rates of PS, ABS, PMMA and PET are still improved, with the average recovery rates of PS, ABS and PMMA increasing to about 40%, and the average recovery rate of PET increasing to 58.3±2.8%. Therefore, the digestion temperature is set to 60℃.
[0109] Example 7 Selection of digestion time
[0110] In order to obtain the optimal recovery rate effect, the present invention sets a series of digestion time gradients, compares the organic mixture removal effect and micro-nano plastic recovery rate at each time length, and thus obtains the optimal digestion time length.
[0111] ① Prepare a micro-nano plastic mixed standard sample according to the method of Example 1;
[0112] ② When the digestion temperature and 2mLHNO3 concentration remain unchanged, a 6h digestion group (n=4), a 4h digestion group (n=4), a 2h digestion group (n=4) and a process blank control group are set up, and the known micro-nano plastic mixed standard sample of each digestion group is placed in an ampoule bottle. The digestion method is as shown in Example 4. The lyophilized sample is subjected to Py-GC / MS analysis according to step (2) of Example 3. The total ion current diagram of the sample is quantified according to steps (3) and (4) of Example 3. The recovery rate is calculated according to formula 3. The final result is as follows: Fig. 9 The removal effect of the organic mixture was investigated at each digestion time, and the operation steps were as shown in Example 5. The removal effect was as shown in FIG. Fig.10 shown.
[0113] The results show that when the digestion temperature is 60℃ and the concentration is 2mL 65% HNO3, the digestion time of 4h and 2h can completely remove the organic mixture. When the digestion time is reduced to 4h, the average recovery rates of PE, PS, ABS, PMMA, PC and PVC are improved, with an increase of 6.8 (PMMA)-16.9% (PVC). When the digestion time is reduced from 4h to 2h, the average recovery rates of PMMA and PET are greatly improved, and the average recovery rates are increased to 62.8±5.9% and 88.0±2.4%, respectively. Therefore, 2h was selected as the optimal digestion time.
[0114] Example 8 Selection of digestion solution concentration
[0115] In order to obtain the optimal recovery rate, this embodiment sets a series of HNO3 concentration gradients to compare the organic matter mixed removal effect and micro-nano plastic recovery rate of different HNO3 concentrations, so as to obtain the optimal HNO3 concentration.
[0116] ① Prepare a micro-nano plastic mixed standard sample according to the method of Example 1;
[0117] ② When the digestion temperature, the volume of the digestion solution and the digestion time remain unchanged, a 65% HNO3 digestion group (n=4), a 32.5% HNO3 digestion group (n=4), a 26% HNO3 digestion group (n=4) and a process blank control group are set up, and the known micro-nano plastic mixed standard sample of each digestion group is placed in an ampoule bottle. The digestion method is as shown in Example 4. The lyophilized sample is subjected to Py-GC / MS analysis according to step (2) of Example 3. The total ion current diagram of the sample is quantified according to steps (3) and (4) of Example 3. The recovery rate is calculated according to formula 3. The final result is as follows: Fig.11 The removal effect of the organic mixture was investigated at each HNO3 concentration. The operation steps were as shown in Example 5. The removal effect was as shown in FIG. Fig.12 shown.
[0118] When the digestion temperature is 60°C and the digestion time is 2h, the 26% HNO3 group cannot completely remove the organic mixture, and only the 32.5% HNO3 group can completely remove the organic mixture, so only the recovery rates of the 65% HNO3 digestion group and the 32.5% HNO3 group are calculated. When HNO3 is reduced from 65% to 32.5%, the average recovery rate of all micro-nano plastics is improved, among which the average recovery rate of PS, ABS and PC is the most significantly improved, and its average recovery rate is increased to more than 60%. Therefore, this embodiment determines that the concentration of 32.5% HNO3 is the optimal concentration. Under this condition, the average recovery rates of PE, PP, PS, ABS, PMMA, PC, PVC and PET are 97.3±13.9, 89.4±6.8, 63.2±2.1, 63.9±8.4, 69.9±6.8, 86.6±14.0, 84.0±24.6 and 91.7±14.3%, respectively.
[0119] Example 9 Evaluation of Digestion Method
[0120] (1) Instruments and reagents
[0121] (2) Gas chromatography-mass spectrometry instrument (Agilent 7890-5975), pyrolyzer (Frontier PY-3030D), high-flow active atmospheric sampler (1m 3 / min, Shanghai Xintuo). 8 kinds of micro-nano plastic pure substances. Quartz fiber filter membrane (Munktell), glass fiber filter membrane (Beijing Mairuida).
[0122] (3) Micro-nano plastic mixture preparation and sample collection
[0123] The eight single labels prepared in Example 1 were measured in different volumes / masses by using a sampling needle / microbalance, and the single labels were mixed to prepare eight mixed labels of micro-nano plastics, with a total of eight portions.
[0124] A high-flow sampler was used to collect 24-hour atmospheric fine particulate matter (PM 2.5 ), the sampling site is located on the platform of the specimen building of Guangzhou Institute of Geochemistry in Tianhe District, Guangzhou City, Pearl River Delta. PM 2.5 The samples were collected on a quartz filter (16 cm × 21 cm) that had been pre-calcined at 450 °C for 6 h (to remove any organic matter that might be present). After sampling, the samples were folded in half and wrapped in clean aluminum foil, sealed in a sealed bag to avoid light, and placed in a -20 °C refrigerator awaiting analysis. Before and after sample collection, the filter membrane was placed in a constant temperature and humidity chamber for 48 h, and then a high-precision balance (Sartorius, ±0.0001 g) was used to weigh the filter membrane before and after sampling. PM was collected 2.5 The weight is the difference between the weight of the filter membrane before and after sampling.
[0125] (4) Double-Shot-Py-GC / MS
[0126] The sample to be tested is placed in the pyrolysis cup, and a certain amount of d-PS internal standard is added using an injection needle. After the internal standard solvent evaporates, the pyrolysis cup is fixed on the injection rod and loaded into the pyrolysis chamber. When the temperature of the pyrolysis chamber reaches 300°C, the injection rod is pushed down, and the pyrolysis cup enters the heating zone of the pyrolysis chamber. After baking the sample for 2 minutes, the injection rod is pulled out. After the pyrolysis chamber is heated to 590°C, the injection rod is pushed down again and GC / MS is started for data acquisition at the same time to obtain the Py-GC / MS total ion flow diagram of the sample at 590°C.
[0127] Double-Shot-Py-GC / MS instrument conditions: The Double-Shot-Py-GC / MS analysis system consists of an Agilent 7890-5975 gas chromatograph-mass spectrometer and an EGA / PY-3030D multi-shot pyrolysis instrument. The ion source uses the electron impact ionization source (EI) mode. The non-polar DB-5MS (30m×0.25mm×0.25um) (Agilent Technologies, Santa Clara, USA) is used as the chromatographic column, the injection port temperature is 280°C, the helium flow rate is 1.1mL / min, the split ratio is 5:1, and the carrier gas is high-purity helium. The heating program is an initial temperature of 40°C, maintained for 2min, increased to 250°C at a rate of 5°C / min, maintained for 1min, and then increased to 300°C at a rate of 1.5°C / min and maintained for 5min. The ion source temperature was 250°C, the transfer line temperature was 295°C, the acquisition mode was scan mode, the scan range was 50-550 m / z, and the solvent delay time was 1.2 min. The multi-shot pyrolysis instrument was set to: thermal desorption at 300°C for 2 min, then increased to 590°C, thermal pyrolysis for 1 min, and the interface temperature was 300°C.
[0128] (5) Sample digestion
[0129] After the sample is placed in the ampoule, add the digestion solution and heat the mouth of the ampoule to seal it. Place the sealed ampoule in the inner tank and add 150μL of water to balance the pressure difference between the inside and outside to prevent the ampoule from exploding. Place the inner tank in the stainless steel outer tank, tighten the outer tank and place it in an oven for heating. After the digestion is completed, take out the digestion tank and take out the ampoule after cooling to room temperature. Place a 0.22μm glass fiber filter membrane with a diameter of 2.5cm in the filtration device and connect it to a vacuum pump. Use a glass dropper to transfer the solution in the ampoule to the filtration device, rinse the ampoule with ultrapure water and transfer it to the filtration device, turn on the vacuum pump to pump the solution on the top of the device into the lower conical flask, and also rinse the upper device with ultrapure water. After drying, take out the glass fiber filter membrane and store it in clean aluminum foil. Use a cold dryer to dry the filter membrane. After the cold drying is completed, perform Py-GC / MS analysis according to the method in step 3.
[0130] (6) Matrix spike experiment
[0131] In order to verify the effectiveness of the above digestion method in treating micro-nano plastics in actual atmospheric samples, 8 portions of the micro-nano plastic mixture of known mass prepared in step (2) were added to a clean quartz fiber filter membrane, and the recovery rate after digestion was measured. The spiked quartz fiber filter membrane was placed in an ampoule, and the sample was digested according to step (4). The digestion conditions were: 2mL32.5% HNO3, 60°C digestion temperature and 2h digestion time; the cooled sample was subjected to Py-GC / MS analysis according to the method of step (3); the obtained Py-GC / MS total ion flow chart was processed and quantified according to the chromatographic peak reconstruction algorithm of Example 3. The final matrix spike recovery results are shown in Figure 2. Fig.13 shown.
[0132] The results showed that the average recovery rates of the eight plastics were 65.02±4.8 (PMMA)-98.3±7.4% (PE). The average recovery rate of the matrix spiked samples was comparable to the average recovery rate of the blank spiked samples in Example 5, indicating that the digestion method can avoid the interference of the matrix effect and effectively retain the micro-nano plastics in the samples. (7) Determination of micro-nano plastics in atmospheric particulate matter samples
[0133] Apply the digestion method of step (2) to actual atmospheric PM 2.5 In order to identify the atmospheric PM 2.5 To obtain uniform sampling, a stainless steel cutter with a diameter of 1 cm was used to filter the quartz fiber filter with an effective area of 16 × 21 cm (sampling volume of 1440 m 3 ) to cut 9 small circular membranes of equal area ( Fig.13 ; 9 small circular membranes with a total area of 4.9m 3 , total sample volume 21m 3), tear off the surface of 9 circular membranes and put them into an ampoule. In order to verify the stability of the method, 5 copies of 9 small circular membranes of equal area were repeatedly sampled on the same quartz fiber filter membrane sample as a parallel control group, and the sample was digested according to step 4. The digestion conditions were: 2mL 32.5% HNO3, 60°C digestion temperature and 2h digestion time. The cooled samples were analyzed by Py-GC / MS according to the method in step 3, and the obtained Py-GC / MS total ion flow chart was processed and quantified according to the chromatographic peak reconstruction algorithm of Example 3. The total concentration of micro-nano plastics in the final 5 parallel control samples is as follows: Fig.14 As shown, the proportion of each micro-nano plastic in the 5 parallel control samples is Fig.15 shown.
[0134] The total concentration of micro-nano plastics in the five parallel control samples ranged from 390.8 to 525.3 ng / m 3 The median concentration was 422.7 ng / m 3 The average total concentration was 447.6 ng / m 3 , the relative standard deviation is 50.6ng / m 3 The proportion of each micro-nano plastic in 5 parallel samples is Fig.16 PE accounted for the highest proportion in 55 samples, accounting for 53.7-64.4% of the total micro-nano plastics, with an average concentration of 266.6±41.9ng / m 3 PVC was the second most abundant substance, accounting for 18.2-23.1% of the total micro-nano plastics, with an average concentration of 93.0±11.9ng / m 3 PET ranks third, accounting for 6.5-8.5% of the total micro-nano plastics, with an average concentration of 31.8±2.6ng / m 3 The remaining micro-nano plastics accounted for about 20% in total, and the proportions from high to low were PC (4.3-6.7%), PMMA (2.9-5.4%), PP (1.2-2.6%), ABS (1.2-1.8%) and PS (0.1-1%), with average concentrations of 23.0±4.1, 15.4±4.3, 9.2±1.8, 6.3±0.7 and 2.3±1.3 ng / m 3 The total concentration of micro-nano plastics and the proportion of each type of micro-nano plastics in the five parallel samples were similar, indicating that the digestion method of the present invention has good stability and that the samples cut out by 9-point sampling are representative.
[0135] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A Py-GC / MS analysis method for micro-nano plastics in atmospheric particulate matter, characterized in that: The micro-nano plastics include PE, PP, PS, ABS, PC, PMMA, PVC and PET. The method comprises the following steps: S1. Preparation of standard samples of micro-nano plastics: Take standard samples of PE, PP, PS, ABS, PC, PMMA, PVC, PET and d-PS, and prepare a mixed solution of dichloromethane and tetrahydrofuran, hexafluoroisopropanol, ethyl acetate and pure silica in a volume ratio of 1:1 respectively; add a mixed solution of dichloromethane and tetrahydrofuran to the PS, PVC, PMMA, ABS or PC standard products to prepare the corresponding liquid single standards; add a hexafluoroisopropanol solution to the PET standard product to prepare a PET liquid single standard; add an ethyl acetate solution to the d-PS standard product to prepare a d-PS liquid single standard; add silica to the PE or PP standard product to prepare the corresponding solid single standard, and the d-PS liquid single standard is used as a quantitative internal standard to correct the error in the thermal cracking process; S2. Selection of quantitative compounds for micro-nano plastics: 8 quantitative compounds for micro-nano plastics and d-PS internal standards were selected, the quantitative compound for PE was 1-eicosene, the quantitative compound for PP was 2,4-dimethyl-1-1heptene, the quantitative compound for PS was 1,3,5-triphenyl-5-hexene, the quantitative compound for ABS was 4-phenyl-4-pentenenitrile, the quantitative compound for PC was p-isopropenylphenol, the quantitative compound for PMMA was methyl methacrylate, the quantitative compound for PVC was indene, and the quantitative compound for PET was benzene; S3. Place the standard sample to be tested in a pyrolysis container, add d-PS internal standard, and after the internal standard solvent evaporates, load the pyrolysis container into the cracker. When the temperature of the cracker reaches 290℃-310℃, the pyrolysis container enters the heating zone of the cracker, bakes the sample for 1.5-2.5 min and then pulls it out. After the cracker is heated to 580℃-600℃, push the injection rod down again and start GC / MS for data acquisition at the same time to obtain the Py-GC / MS total ion flow diagram of the sample. The detection conditions of GC / MS are as follows: non-polar DB-5MS 30 m×0.25 mm×0.25 μm Agilent Technologies, Santa Clara, USA as the chromatographic column, the injection port temperature is 280℃, the helium flow rate is 1.1 mL / min, the split ratio is 5:1, and the carrier gas is high-purity helium; the heating program is as follows: initial temperature 40℃, hold for 2 min, increase to 250℃ at a rate of 5℃ / min, hold for 1 min, then increased to 300℃ at 1.5℃ / min and maintained for 5 min; the ion source used electron impact ionization source (EI) mode, the ion source temperature was 250℃, the transfer line temperature was 295℃, the acquisition mode was scan mode, the scan range was 50-550 m / z, and the solvent delay time was 1.2 min; the multi-shot pyrolysis instrument was set as follows: thermal desorption at 300℃ for 2 min, then increased to 590℃, thermal pyrolysis for 1 min, and the interface temperature was 300℃; S4, measuring the solid / liquid single label configured in step S1 according to the measurement conditions of step S3 by using a chromatographic peak reconstruction algorithm, and extracting the quantitative compound selected in step S2 from the total ion current graph of each single label; The implementation steps of the algorithm are as follows: (1) A series of mass gradient micro-nano plastic mixed standard samples were prepared by adding six liquid single standards of PS, ABS, PC, PMMA, PVC, and PET in different volumes and two solid single standards of PE and PP in different masses. The micro-nano plastic mixed standard samples were analyzed by Py-GC / MS. The quantitative compound ion chromatograms of the mutually interfering micro-nano plastics and internal standards were extracted from the total ion flow diagram, and the response factor of each quantitative compound was calculated. The quantitative compound response factors of the mutually interfering micro-nano plastics can form a matrix. (2) Py-GC / MS was used to analyze a series of mass gradient single standards of five mutually interfering micro-nano plastics, namely PE, PS, ABS, PVC and PET. The quantitative compound ion chromatograms of the five mutually interfering micro-nano plastics and the internal standard were extracted from all total ion currents. Assuming that the yields of all pyrolysis products during the pyrolysis of micro-nano plastics were constant, a linear equation for the response factor ratio of the quantitative compound of the micro-nano plastic and other quantitative compounds of the generated micro-nano plastics was established based on the series of mass gradient single standards of each micro-nano plastic. The linear equation group of the response factor ratio of mutually interfering micro-nano plastics constituted the contribution matrix of the nonspecific quantitative compound source. (3) Assuming that the nonspecific pyrolysis products in the micro-nano plastic mixture mainly come from the linear combination of the pyrolysis contributions of the mutually interfering micro-nano plastics, the response factor matrix of the mutually interfering micro-nano plastic quantitative compounds obtained from the micro-nano plastic mixed standard and the nonspecific quantitative compound source contribution matrix obtained from the single standard are solved. The result is the chromatographic peak reconstruction matrix, that is, the actual quantitative compound response factor matrix of the mutually interfering micro-nano plastics; (4) Repeatedly solve the chromatographic peak reconstruction matrix of each mass gradient micro-nano plastic mixed standard sample, and establish the quantitative standard curve of each micro-nano plastic with the actual quantitative compound response factor of the micro-nano plastic as the horizontal coordinate and the mass as the vertical coordinate; S5. Add digestion solution to the atmospheric particulate matter sample for digestion. After digestion is completed, filter the sample and freeze-dry it for analysis; S6. Detect the atmospheric particulate matter sample obtained in step S5 according to the detection conditions of step S3, and perform qualitative and / or quantitative analysis on the Py-GC / MS total ion current diagram of the obtained atmospheric particulate matter sample.
2. The analysis method according to claim 1, characterized in that In step S1, the liquid single-label concentrations of PS, PVC, PMMA, ABS, PC and PET are all 1.0-1.5 µg / µL, and the solid single-label concentrations of PP and PE are all 2-4 µg / mg.
3. The analysis method according to claim 1, characterized in that The quantitative compound of the internal standard d-PS in step S2 is styrene-D7.
4. The analysis method according to claim 1, characterized in that The quantitative standard curves of each micro-nano plastic in step S4 are shown in the following table: 。 5. The analysis method according to claim 1, characterized in that In step S5, the digestion solution is nitric acid, trifluoroacetic acid or hydrogen peroxide, and the volume concentration of the digestion solution is 26%-65%.
6. The analysis method according to claim 5, characterized in that The ratio of atmospheric particulate matter sample to digestion solution is: add 1.04-2.60 mL of digestion solvent to 1 mg of atmospheric particulate matter sample.
7. The analysis method according to claim 1, 5 or 6, characterized in that: The digestion time is 2-6 h, and the digestion temperature is 60℃-100℃.
8. The analysis method according to claim 1, characterized in that The qualitative and / or quantitative analysis of the Py-GC / MS total ion current diagram of the atmospheric particulate matter sample obtained in step S6 is specifically as follows: Qualitative analysis: extract the quantitative compound ion chromatogram of each micro-nano plastic selected in step S2 from the total ion current of Py-GC / MS. If the corresponding quantitative compound ion can be extracted, it means that the sample contains the micro-nano plastic; Quantitative analysis: For the five micro-nanoplastics, PE, PP, PMMA, PC and ABS, the quantitative compound ion chromatograms of these five micro-nanoplastics and the internal standard are extracted from the total ion current map, the response factor of each quantitative compound is calculated, and the response factor is substituted into the corresponding micro-nanoplastic quantitative standard curve in step S4 to obtain the mass of the micro-nanoplastic in the sample; for the three micro-nanoplastics, PET, PVC and PS, the quantitative compound ion chromatograms of these three micro-nanoplastics and the internal standard are extracted from the total ion current map, the quantitative compound response factors of the three micro-nanoplastics and their corresponding mutually interfering micro-nanoplastics are calculated, and the quantitative compound response factor matrix of the mutually interfering micro-nanoplastics and the corresponding non-specific quantitative compound source contribution matrix in step S4 are solved to obtain the actual quantitative compound response factors of the mutually interfering micro-nanoplastics in the sample, which are substituted into the corresponding micro-nanoplastic quantitative standard curve in step S4 to obtain the mass of the micro-nanoplastic in the sample.
9. Application of the analytical method of claim 1 in the determination of micro-nano plastics in atmospheric particulate matter, characterized in that: The micro-nano plastics include PE, PP, PS, ABS, PC, PMMA, PVC and PET.
Citation Information
Patent Citations
Method for detecting nano-plastics in biological tissues
CN112229921A
Py-GC / MS analysis method for micro-plastics in agricultural soil
CN112505182A